1980
DOI: 10.1016/0015-6264(80)90104-2
|View full text |Cite
|
Sign up to set email alerts
|

In vivo covalent binding of aflatoxin metabolites isolated from animal tissue to rat-liver DNA

Abstract: Abstract-Ring-labelled [ 14 C)aftatoxin 8 1 (AFB.), prepared by biosynthesis. or ~enerally Iabeiied [ 3 H]AFB 1 was administered by oral gavage to young adult _male rat~. After 6 hr. ~he hver _w~~ removed and two fractions were isolated, namely macromolecules, wh1ch contamed about 3 /o of the lmtlal dose of AFB 1 radioactivity. and water-soluble. low-molecular aftatoxin conjugates containing about_0·2~~~ of the administered radioactivity. These two fractions were administered orally to other rats ·~ o~der to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Results of the present study demonstrate that the pig rapidly metabolizes and clears its tissues of aflatoxins on feeding an uncontaminated diet. This adds further support to the conclusions of Jaggi et al (1980) that the risk from eating liver or meat of animals fed an aflatoxincontaminated diet are negligible. trichothecolone (3), and trichothecin (4), were isolated and characterized from anise fruits infected in fields with Trichothecium roseum van Beyma (CMI-IMI 225229).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Results of the present study demonstrate that the pig rapidly metabolizes and clears its tissues of aflatoxins on feeding an uncontaminated diet. This adds further support to the conclusions of Jaggi et al (1980) that the risk from eating liver or meat of animals fed an aflatoxincontaminated diet are negligible. trichothecolone (3), and trichothecin (4), were isolated and characterized from anise fruits infected in fields with Trichothecium roseum van Beyma (CMI-IMI 225229).…”
Section: Discussionsupporting
confidence: 74%
“…Earlier work on in vivo covalent binding of aflatoxin metabolites led Jaggi et al (1980) to conclude that macromolecular bound aflatoxin Bx was at least 4000 times less active than B, per se with respect to binding to rat liver DNA, whereas the water-soluble conjugates were at least 100 times less potent than aflatoxin Bx itself. On this basis, they concluded that the risk to humans consuming liver or meat containing aflatoxin residues is negligible compared to that from consuming other aflatoxin-contaminated foods, such as nuts or milk.…”
Section: Discussionmentioning
confidence: 99%
“…The macromolecular fraction containing the bound aflatoxin residues was subsequently administered to a second rat. No radioactivity was detectable on the liver DNA of the second rat (44). This means, that the binding capacity of these macromolecular metabolites is at least 4 000 times less than that of aflatoxin B1.…”
mentioning
confidence: 80%
“…This irreversibility has been confirmed in recent years by many investigations. The work of Jaggi and his co-workers (Jaggi et al 1980) on in vivo covalent binding of aflatoxin metabolites isolated from animal tissues to rat-liver DNA is a particularly good example: aflatoxin Bl has a covalent-binding index (CBI) of DNA of 10 000. This Downloaded by [New York University] at 06:44 06 August 2015…”
Section: Mechanism and Characteristics Of Covalent Bindingmentioning
confidence: 99%